2017
DOI: 10.1007/s00415-017-8591-z
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous EEG–PET–fMRI measurements in disorders of consciousness: an exploratory study on diagnosis and prognosis

Abstract: Previous studies could demonstrate that functional magnetic resonance imaging (fMRI), fludeoxyglucose positron emission tomography (FDG-PET), and electroencephalography (EEG) measures contain information about patients suffering from disorders of consciousness (DOC) and thus improve the clinical diagnosis. Additionally, the technical modalities were able to predict the outcome of patients. However, most studies lack proven reproducibility in a clinical setting. We here applied a standardized combined EEG/fMRI/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 48 publications
0
18
0
Order By: Relevance
“…PICO questions 1–3 refer to resting state PET and fMRI, PICO questions 4–6 to passive and active fMRI paradigms. Forty‐four publications were included for final analysis . PICO 1 Should resting state PET be used to diagnose signs of covert consciousness in patients with DoC? …”
Section: Resultsmentioning
confidence: 99%
“…PICO questions 1–3 refer to resting state PET and fMRI, PICO questions 4–6 to passive and active fMRI paradigms. Forty‐four publications were included for final analysis . PICO 1 Should resting state PET be used to diagnose signs of covert consciousness in patients with DoC? …”
Section: Resultsmentioning
confidence: 99%
“…Golkowski et al (2017) acquired BOLD-fMRI, FDG-PET and EEG in people with disorders of consciousness (minimally conscious/comatose). Golkowski et al (2017) acquired BOLD-fMRI, FDG-PET and EEG in people with disorders of consciousness (minimally conscious/comatose).…”
Section: Mr-pet Receptor Imagingmentioning
confidence: 99%
“…Trimodal neuroimaging is also possible on commercially available simultaneous MR-PET scanners. Golkowski et al (2017) acquired BOLD-fMRI, FDG-PET and EEG in people with disorders of consciousness (minimally conscious/comatose). They found that FDG-PET but not EEG or BOLD-fMRI was significantly higher in minimally-conscious people compared to people with unresponsive wakefulness syndrome, and FDG-PET was related to the clinical rating of consciousness.…”
Section: Mr-pet Receptor Imagingmentioning
confidence: 99%
“…The relationship between simultaneously recorded bimodalities, such as fMRI/PET (Aiello et al, 2015; Riedl et al, 2014, 2015), fMRI/EEG (Goldman, Stern, Engel, & Cohen, 2000; Huster, Debener, Eichele, & Herrmann, 2012; Ritter & Villringer, 2006) and PET/EEG (Hur, Lee, Lee, Yun, & Kim, 2013), has already been reported by a number of groups. Furthermore, other research has shown the feasibility and application (Golkowski et al, 2017; Del Guerra et al, 2017; Shah et al, 2017) of simultaneous trimodal (MR/PET/EEG) measurements. Even though various functional relationships between simultaneously recorded bimodal and trimodal data have already been investigated and reported on, an exploratory analysis on the neuroelectric (electrophysiology as measured by EEG) metrics and its relationship with neurovascular (hemodynamic response as measured by BOLD fMRI) and neurometabolic (metabolic activity as measured by PET) metrics on a simultaneously recorded resting state (rs) trimodal data set has not yet been reported.…”
Section: Introductionmentioning
confidence: 99%